(untitled) (Journal of Environmental Science and Natural Resources, 2016)
Feeding propensity and cannibalism of Micraspis discolor (Fab.) to different prey species (bean aphids and brown plant hopper ) was studied in the laboratory of the Department of Entomology, Bangladesh Agricultural University, Mymensingh, during January, 2007 to April, 2007. It was found that the highest pre-oviposition period was to 5.6±0.54 days when BPH were used and this period was lowest, 4.6±0.54 days using bean aphid. The oviposition period was maximum 40.20±1.78 days using bean aphid and minimum 29.00± 2.00 days were found using BPH. Maximum number of eggs 216.00±16.58 was laid when fed on bean aphid. The hatching percent was highest 88.71% using bean aphid and hatching percent was lowest 85.34% when fed on BPH. Incubation period varied from 2.40±0.54 to 3.80±0.44 days using different foods. However, the larvae passed through four larval instars and highest larval period was 10.00 ± 0.70 when BPH were used as food and lowest was 8.40 days feeding on bean aphid. Pupal period was 3.00±0.00 & 3.80±0.44 days when bean aphid & BPH were supplied as food. The average longevity of female was 38.60±3.78 and 31.40±2.96 days and that of male was 32.00±2.91 & 26.00±0.91 days when feeding on bean aphid and BPH respectively. It was significant at 1% level. The sex ratio of male and female was found (0.78:1.00) using different foods and these were not significant at 1% level. By this experiment, It was observed that feeding propensity of Micraspis discolor to different prey species during the total life cycle was as follows: bean aphid > BPH. It was also found that M. discolor had cannibalistic behavior and this was significant at 1% level. J. Environ. Sci. & Natural Resources, 9(1): 81-85 2016